2019
DOI: 10.1186/s13063-018-3157-7
|View full text |Cite
|
Sign up to set email alerts
|

Promoting Help-seeking using E-technology for ADolescents with mental health problems: study protocol for a randomized controlled trial within the ProHEAD Consortium

Abstract: BackgroundThe highest incidence and prevalence of mental health problems across the lifespan as well as the first onset of most long-term mental health conditions are reported for youths between 14 and 25 years of age. At the same time, only 25% of adolescents with mental health problems receive professional treatment. One explanation for poor treatment access in youths is their low help-seeking behavior. Barriers that can keep children and adolescents (C&A) from seeking professional help include a lack of per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 42 publications
0
23
0
1
Order By: Relevance
“…Counselling centers in academic institutions are readily available to provide services to help students with mental illness, however, the stigma attached to consulting school counselors deter students from accessing these services [ 7 ]. Help-seeking behavior remains one of the main bottlenecks in mental health due to factors such as stigma, embarrassment, and problems recognizing symptoms [ 8 , 9 ]. Help-seeking behavior refers to a complex decision-making process that is triggered by a problem that challenges the capabilities of an individual [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Counselling centers in academic institutions are readily available to provide services to help students with mental illness, however, the stigma attached to consulting school counselors deter students from accessing these services [ 7 ]. Help-seeking behavior remains one of the main bottlenecks in mental health due to factors such as stigma, embarrassment, and problems recognizing symptoms [ 8 , 9 ]. Help-seeking behavior refers to a complex decision-making process that is triggered by a problem that challenges the capabilities of an individual [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Each item of BDI-II is scored on a four-point Likert scale from 0 (symptom absent) to 3 (severe symptoms). The sum of BDI-II scores classi cation is as follows: Normal depression (0-13), mild depression(14)(15)(16)(17)(18)(19), moderate depression (20-28), or severe depression (29-63). The I.P.Q.-R has illustrated adequate reliability and validity[51].…”
mentioning
confidence: 99%
“…Globally, about 10-20% of children and adolescents have mental health problems [1,2]. Several studies depicted that most of mental health problems in adulthood essentially start to happen during adolescence [3,4]. A worldwide-pooled meta-analysis from all regions of the world from twenty seven countries reported that about 13.4% child and adolescent have mental disorders [5].…”
Section: Introductionmentioning
confidence: 99%
“…Empirical studies have shown that most of adolescents having mental health problems have usually limitation in help seeking and delay to get timely help [4,[9][10][11]. A number of adolescents do not recognize how and when to get help for their mental health difficulties [12].…”
mentioning
confidence: 99%
See 1 more Smart Citation